Strengthening Academic Awareness and Character Education among Students: A Study of IAIN Pontianak’s International Academic Program in Malaysia - Ramadhan, Ahmad Fadhail; Sahri, Sahri; Jabbar, Luqman Abdul; Hamzah, Nur (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to analyze the role of international academic programs in enhancing academic awareness and character education for postgraduate students at the State Islamic Institute (Institut Agama Islam Negeri Pontianak/IAIN) Pontianak. This study uses descriptive qualitative research in which the author is directly involved as a participant in the international academic program conducted in Malaysia. The research subjects include IAIN Pontianak students and lecturers involved in the program, with the activity location at SMK Pesantren Abdul Taib Mahmud, Sarawak, Malaysia. Data collection techniques were carried out through participant observation, interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research results indicate that international academic programs significantly contribute to strengthening students’ academic awareness through direct involvement in teaching activities, academic presentations, and cross-cultural interactions. Furthermore, these programs play a role in the internalization of character education relevant to Islamic educational values. However, the implementation of international academic programs also faces various challenges, requiring institutions to be prepared to design structured and sustainable programs for their success. Strengthening pre-departure orientation, providing language and cultural training, and faculty mentoring are important strategies to minimize challenges and maximize the benefits of the program. This study confirms that international academic programs serve as a strategic means in shaping Islamic Studies Master’s graduates who are globally minded, possess Islamic character, and are capable of contributing to the global community.